Long-term effects of conditional cash transfers on children: the brazilian case - Oliveira, Gabriel Lyrio de (2020)
In this dissertation, I present some long-term effects of the largest Conditional Cash Transfers program in the world, and one of the pioneers, the Bolsa Família Program (BFP). I focus on the effects on Schooling attained in early adulthood and Labor Market outcomes of individuals more or less exposed during their childhood. The estimates were enabled by linking identified data from Formal Labor Market, BFP payment records, and the Single Registry (SR). I focus the analysis on the differential effects of different durations of exposure divided into levels. In this Natural Experiment, our main identification strategy relies on a rich set of control variables, and on the fact that the release of BFP resources for registered families is automatized and based on municipality poverty parameters estimated by the government. Beyond the individual\'s demographics, I consider observable family characteristics related to their childhood, like the schooling and labor market outcomes of their parents. In an alternative identification strategy, I consider an instrumental variable, the observed proxy for the municipality effort to register vulnerable families. These strategies help to solve the potential selection bias of families to the SR, and consequently to the treatment. Nonetheless, since the program selects the most vulnerable families, the threats to the identification suggest that the estimates are lower bounds. The main results show positive long-term effects of the BFP exposure on Schooling, and on the Formal Labor Market participation, while mixed results are observed for Earnings. Heterogeneity tests suggest that the effects are stronger for boys, for smaller cities, and for families with never formally employed parents.